Structure, hardness and thermal stability of TiAlBN coatings grown by alternating deposition of TiAlN and BN - Park, Jong-Keuk; Cho, Jong-Young; Jeon, Hyeong-Tag; Baik, Young-Joon (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Hardness and thermal stability of TiAlBN coatings prepared by alternating deposition of TiAlN and BN with high rotation speed of substrate holder (similar to 7 rpm) have been investigated. The TiAlN and BN were deposited by reactive sputtering of Ti0.5Al0.5 and BIN targets with N-2 and At reactive gases. respectively. Despite alternating deposition, the TiAlBN coating did not show layered structure due to high rotation speed of substrate holder. By TEM analysis, the TiAlBN coating was observed to be nanocomposite with grain less than 10 nm in size. Compared to TiAlN coating, the TiAlBN nanocomposite coating showed superior hardness. Furthermore, the hardness of the coating increased after the heat-treatment in N-2 atmosphere up to 800 degrees C. By comparison with TiAlN/BN nanoscale multilayered coating prepared by the same deposition method except the lower rotation speed of substrate holder (similar to 1 rpm), the hardness enhancement after annealing, 'self-hardening', of the TiAlBN nanocomposite coating is believed to be due to the sharpness in chemical composition at the interface between TiAlN and BN phase. (C) 2009 Elsevier Ltd. All rights reserved
Keywords: SUPERLATTICE; PERFORMANCE